Codes of Practice for Northern Ireland issued by the Department of Justice under the Proceeds of Crime Act 2002 : Amendments to three existing codes and a new code to reflect the commencement of the relevant provisions of the Criminal Finances Act 2017 in Northern Ireland.: Amendments to three existing codes and a new code to reflect the commencement of the relevant provisions of the Criminal Finances Act 2017 in Northern Ireland. ([2020]) - Northern Ireland., Department of Justice
No abstract available